2017
DOI: 10.1186/s13033-017-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

What are “good outcomes” in public mental health settings? A qualitative exploration of clients’ and therapists’ experiences

Abstract: BackgroundThe mental health field sees a surge of interest in Routine Outcome Monitoring, mandated by a wish to help better those not-on-track to recovery. What constitutes positive outcomes for these patients is not fully understood.AimsTo contribute knowledge into what constitutes meaningful outcome concepts in the experiences of patients with long and complex mental health suffering and treatment, and the clinicians who work to help them.MethodsA qualitative in-depth study of 50 participants’ experiences. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
(42 reference statements)
0
26
0
Order By: Relevance
“…26,[48][49][50] Two recent taxonomies emphasized the importance of measuring domains beyond symptoms, 17,20 as did a small number of qualitative studies. 51,52 However, with the exception of 1 study, 53 none of the reviewed studies referred to this emerging literature or discussed their measurement approach from a multidimensional perspective.…”
Section: Discussionmentioning
confidence: 99%
“…26,[48][49][50] Two recent taxonomies emphasized the importance of measuring domains beyond symptoms, 17,20 as did a small number of qualitative studies. 51,52 However, with the exception of 1 study, 53 none of the reviewed studies referred to this emerging literature or discussed their measurement approach from a multidimensional perspective.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know whether these changes reflect unequivocal success or successful progress along a journey towards achieving desired personal goals and well‐being. Moltu et al () found that participants at the ‘severe end of mental health suffering’ (p. 3) experienced symptom elimination as less important than having built meaningful ways of living with challenging conditions. Further research involving clients who fail to show improvement or who worsen would help clarify what it means to both clinicians and outcome researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the findings of this case are highly consistent with the ways in which clients describe positive outcomes, in the context of qualitative interviews carried out after the end of therapy. Moltu et al (2017) found that clients described themselves as having used dialogue with their therapist to develop new coping strategies and a deeper sense of acceptance of aspects of self, which then made it possible to be resolute in facing up to life situations and issues that had previously been avoided. The process of purposeful engagement with issues was informed by feedback from other people with significant roles in their everyday life.…”
Section: Discussionmentioning
confidence: 99%